Proceedings of the 8th ACM European Conference on Computer Systems 2013
DOI: 10.1145/2465351.2465373
|View full text |Cite
|
Sign up to set email alerts
|

RadixVM

Abstract: RadixVM is a new virtual memory system design that enables fully concurrent operations on shared address spaces for multithreaded processes on cache-coherent multicore computers. Today, most operating systems serialize operations such as mmap and munmap, which forces application developers to split their multithreaded applications into multiprocess applications, hoard memory to avoid the overhead of returning it, and so on. RadixVM removes this burden from application developers by ensuring that address space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Similarly, from opt nodes to max nodes, the request execution time increases 3.4× and the tail latency increases 21.0×. The experiments with a single thread for all the studied applications except MySQL and SQLite 23 are available in the Appendix ( §D). Overall, we found that, on the studied applications with a single-threaded configuration, the choice of a lock has very little effect on the throughput or the tail latency of the application.…”
Section: How Does Tail Latency Behave When Locks Suffer From High Levels Of Contention?mentioning
confidence: 99%
“…Similarly, from opt nodes to max nodes, the request execution time increases 3.4× and the tail latency increases 21.0×. The experiments with a single thread for all the studied applications except MySQL and SQLite 23 are available in the Appendix ( §D). Overall, we found that, on the studied applications with a single-threaded configuration, the choice of a lock has very little effect on the throughput or the tail latency of the application.…”
Section: How Does Tail Latency Behave When Locks Suffer From High Levels Of Contention?mentioning
confidence: 99%
“…Moreover, mapping virtual memory in a scalable fashion, e.g. as in RadixVM [6], does not solve the problem of designing a competitive allocator. Memory fragmentation and systemcall overhead still need to be managed.…”
Section: Related Workmentioning
confidence: 99%
“…Note that recent Linux kernels provide the ability to use transparent huge pages 6 as backing store for regular pages, i.e., huge pages can be used by the kernel as physical page frames for regular pages. Since this feature interferes with any mechanism relying on on-demand paging, e.g.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 2 more Smart Citations